Prediction of activity coefficient of sulfones at infinite dilution in ionic liquids and their modeling using COSMO-RS - Matheswaran, P. (American Institute of Physics Inc., 2016)
Ionic liquids gained lot of attention as alternate liquids for different task. This work predicts the activity coefficient at infinite dilution in several cases of ILs using conductor-like screening model for real solvents for interaction with different forms of sulfones. 1-Ethyl-1-methylpyrrolidinium chloride has been screened by COSMO-RS as a potential IL for interaction with different forms of sulfones. Â© 2016 Author(s).